2017
DOI: 10.1002/cssc.201701127
|View full text |Cite
|
Sign up to set email alerts
|

Selective Semihydrogenation of Alkynes Catalyzed by Pd Nanoparticles Immobilized on Heteroatom‐Doped Hierarchical Porous Carbon Derived from Bamboo Shoots

Abstract: Highly dispersed palladium nanoparticles (Pd NPs) immobilized on heteroatom-doped hierarchical porous carbon supports (N,O-carbon) with large specific surface areas are synthesized by a wet chemical reduction method. The N,O-carbon derived from naturally abundant bamboo shoots is fabricated by a tandem hydrothermal-carbonization process without assistance of any templates, chemical activation reagents, or exogenous N or O sources in a simple and ecofriendly manner. The prepared Pd/N,O-carbon catalyst shows ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…[11][12][13] Previous studies have demonstrated that the interactions between catalytic speciesa nd the support play significant roles in the catalytic activity and stability. [24][25][26] Nitrogen doping can efficiently promote the overall catalytic activity and selectivityb ym odifying the interactions between In this study,n itrogen-doped graphene nanoshells (N-GNS) were developedt os upport palladium nanoparticles (Pd/N-GNS) as an efficient and recyclable catalyst for the N-allylation reaction. ],c arbon materials provide versatile substrates for metallicc atalysts owing to their unique physicochemical properties, such as controllable morphology, high surfacea rea, thermala nd chemical stability, and the availability for chemical modifications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Previous studies have demonstrated that the interactions between catalytic speciesa nd the support play significant roles in the catalytic activity and stability. [24][25][26] Nitrogen doping can efficiently promote the overall catalytic activity and selectivityb ym odifying the interactions between In this study,n itrogen-doped graphene nanoshells (N-GNS) were developedt os upport palladium nanoparticles (Pd/N-GNS) as an efficient and recyclable catalyst for the N-allylation reaction. ],c arbon materials provide versatile substrates for metallicc atalysts owing to their unique physicochemical properties, such as controllable morphology, high surfacea rea, thermala nd chemical stability, and the availability for chemical modifications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,n itrogendoped carbon materials have been reported to be promising matrixes for Pd NPs in variousc hemical transformations. [24][25][26] Nitrogen doping can efficiently promote the overall catalytic activity and selectivityb ym odifying the interactions between In this study,n itrogen-doped graphene nanoshells (N-GNS) were developedt os upport palladium nanoparticles (Pd/N-GNS) as an efficient and recyclable catalyst for the N-allylation reaction. N-GNS was synthesized through af acile hard-template method by using petroleuma sphalt, followed by nitrogen doping by thermal annealing with urea, the contents and specieso fw hich could be altered by the calcination temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,avariety of biomass materials (e.g.,p ig bone, [24] fish scale, [25] barley straw, [26] and bamboo) [27] have been employed as precursors to synthesize HPCs, due to their versatile microstructures, rich heteroatom elements ands ustainable resource.A mong them, animal bones that possess au nique three dimensional( 3D) ordered microstructure, with apatite minerals being sandwiched among the collagen fibrils, are regarded as the promising precursors for the synthesis of HPCs. [28] The collagen fibrilsi na nimal bones are attractive as the carbon precursors, with nitrogen as dopant, to form Ndoped carbon materials, while the apatite mineralsc an act as ah ard template to control the porous structure,r esulting in a 3D hierarchically porousc arbon network with rich N-doping and large SSA.…”
Section: Introductionmentioning
confidence: 99%
“…For the preparation of N,O‐dual doped porous carbon, the fresh bamboo shoots were pretreated by slice, dry at 70 °C for 12 h and followed by grinding into powder for the hydrothermal process, and subsequently calcined at 850 °C in N 2 flow to produce the porous carbons(Figure ) …”
Section: Pd Nanoparticles Supported On No‐dual Doped Hierarchical Pomentioning
confidence: 62%